Effective Classroom Management in Learning Islamic Cultural History - Afiyatun Kholifah; Alya Syifa Maulida; Ibnu Ma’arif Ainur; Laila Maftuhah Hasyim (Konsultan Jurnal Ilmiah Indonesia, 2026)
Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) learning plays an important role in developing students’ understanding as well as character. This is because SKI learning not only presents historical events but also contains moral values and exemplary lessons that can be applied in daily life. This article aims to analyze effective classroom management in SKI learning by examining its concepts, principles, approaches, as well as supporting and inhibiting factors that influence the success of the learning process. This study employs a library research method by reviewing various relevant sources, including books, scientific journals, and previous studies, which are then analyzed descriptively to obtain a comprehensive understanding of the topic. The findings indicate that effective classroom management is characterized by teachers’ friendly and enthusiastic attitudes, the use of varied teaching methods, flexibility in instruction, and the implementation of positive discipline. Classroom management approaches that can be applied include authority, freedom, socio-emotional, group process, and behavior modification approaches, adjusted to classroom conditions. Supporting factors include a comfortable learning environment, harmonious social relationships, and the availability of adequate learning media. Meanwhile, the obstacles encountered include an excessive number of students, limited facilities, and the use of less varied teaching methods. In conclusion, creative and innovative classroom management can enhance students’ motivation, participation, and understanding of SKI materials. Therefore, teachers need to create a conducive learning environment in order to achieve learning objectives optimally.